Ternary All‐Small‐Molecule Solar Cells with Two Small‐Molecule Donors and Y6 Nonfullerene Acceptor with a Power Conversion Efficiency over Above 14% Processed from a Nonhalogenated Solvent. Issue 11 (13th September 2020) - Guijarro, Fernando G.; Caballero, Rubén; de la Cruz, Pilar; Singhal, Rahul; Langa, Fernando; Sharma, Ganesh D.
Abstract : An efficient organic solar cell (OSC) based on a ternary active layer consisting of two conjugated small‐molecule (SM) donors (FG3 and FG4 ) and a well‐known nonfullerene SM acceptor (Y6 ) is fabricated using a nonhalogenated solvent. An overall power conversion efficiency (PCE) of 14.31% is achieved, higher than that for the binary counterparts, i.e., 10.75% and 11.07% for FG3 :Y6 and FG4 :Y6, respectively. The short‐circuit current density ( J SC ) of the ternary active layer organ is related to the broader absorption spectra when compared with the binary active layers. The open‐circuit voltage ( V OC ) of the ternary active layer‐based OSCs falls between those of the OSCs based on FG3 :Y6 and FG4 :Y6, a situation that is consistent with the lowest unoccupied molecular orbital (LUMO) level of both SM donors (FG3 and FG4 ), and forms the alloy between the two donors. The overlap of the absorption spectra of FG4 with the photoluminescence of FG3 confirms the energy transfer from FG3 to FG4 and this leads to improvement in J SC . The balanced charge transport, reduced charge recombination, and the fast charge extraction in the ternary active layer leads to the higher fill factor (FF) value. A combination of all of these effects affords a high PCE value. Abstract : The combination of two well‐defined conjugated small‐molecule (SM) donors FG3 and FG4 and Y6 as well‐known nonfullerene SM acceptors provides the fabrication of efficient ternary OSCs. This contribution shows an excellent power conversion efficiency (PCE) of 14.31% with a high fill factor (FF) and J sc, in contrast with the binary counter parts.